Answer:
4x^2 -16
Step-by-step explanation:
(2x + 4)(2x - 4)
FOIL
first:2x*2x = 4x^2
outer: -4 *2x = -8x
inner: 4*2x = 8x
last: -4*4 = -16
Add them together
4x^2 -8x+8x =-16
4x^2 -16
The multiplication of the expression (2x + 4)(2x - 4) is 4x² - 16.
Given the expression in the question:
(2x + 4)(2x - 4)
We can multiply the expression (2x + 4)(2x - 4) using the distributive property and the FOIL method.
(2x + 4)(2x - 4)
Apply the FOIL method:
2x( 2x - 4 ) + 4( 2x - 4 )
Apply distributive property:
2x × 2x + 2x × - 4 + 4 × 2x 4 × - 4
Multiply the terms:
4x² - 8x + 8x - 16
Collect and add like terms:
4x² - 16
Therefore, the simplified form is 4x² - 16.
Learn more about the FOIL method here: brainly.com/question/27980306
#SPJ6
Answer:
1085
Step-by-step explanation:
100 - 69 =31%
3500 /100 =35
35 x 31 = 1085
Answer: you would pay 1085
Answer:
q=35
Step-by-step explanation:
x2 - 12x + q = 0
Let the two roots be r and r+2.
Factor the quadratic expression:
(x - r)[x - (r + 2)] = 0
Expand, simplify, group like terms, and get
x2 - 2(r + 1)x + r(r + 2) = 0
Compare to
x2 - 12x + q = 0
and set equal the coefficients of like terms:
Coefficient of x:
-2(r + 1) = -12 ⇒ r + 1 = 6 ⇒ r = 5
(Then the other root is r + 2 = 5 + 2 = 7)
Constant term:
r(r + 2) = q ⇒ 5(5 + 2) = q
q = 35
Test the solution:
(x - 5)(x - 7) = x2 - 12x + 35
With two roots differing by 2, you get an equation of the form
x2 - 12x + q = 0
with q = 35.